Trueness and Precision of Eight Intraoral Scanners with Different Finishing Line Designs: A Comparative In Vitro Study - Falih, Mina Yahia; Majeed, Manhal A. (European Journal of Dentistry, 2022)
Objective This study aimed to evaluate the accuracy in terms of trueness and precision of eight intraoral scanners (IOS) and the effect of different finishing line designs on the IOS's accuracy.Materials and Methods Three printed models of the maxillary arch with maxillary right first molar virtually prepared with chamfer, shoulder, and vertical preparation designs were used as master models in this study. Each model was scanned 30 times with each IOS: Medit i700, Planscan Emerald S, CEREC Primescan, TRIOS 3, CS3600, MEDIT i500, Heron 3Disc, and Cerec Omnicam. The trueness was measured by superimposition of the scanned dataset made with IOS and the scanned dataset made with a lab scanner (In Lab Medit T710) that was used as a reference and the deviation was measured and expressed as a color-coded map by the metrology program (Medit compare, version 2.3.5.892), while precision was measured by the superimposition of the scans of each IOS on each other.The data were analyzed statistically using repeated measure analysis of variance (ANOVA) test, one-way ANOVA test, and Bonferroni test at significance level of 0.05.Results The tested IOS showed significant differences in trueness and precision. Medit i700 and CEREC Primescan recorded the highest precision with no significant difference between them, while Medit i700 recorded the highest trueness as compared to other IOS. Each IOS showed significant differences in trueness and precision with the three finishing line designs except CEREC Primescan and Heron 3 disc that showed no significant difference in trueness with the three finishing line designs and CS3600 that showed no significant difference in precision with the three finishing line designs.Conclusion A significant difference in accuracy was found among the tested IOS and the type of finishing line design had a significant effect on IOS's accuracy.
Keywords: accuracy; intraoral scanner; finishing line; digital dentistry